2012
DOI: 10.1007/s10047-012-0628-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful implantation of HeartWare HVAD left ventricular assist device with concomitant ascending and sinus of valsalva aneurysms repair

Abstract: Coexistence of aortic disease is an uncommon finding in end-stage heart failure patients requiring left ventricular assist device (LVAD) placement. A 38-year-old man with non-ischemic dilated cardiomyopathy was admitted in stage D heart failure. Preoperative computed tomography demonstrated multiple saccular aneurysms of the ascending aorta and sinus of valsalva. We successfully performed complex aortic surgery and the implantation of a continuous-flow LVAD (HeartWare HVAD) (HeartWare International, Framingham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Furthermore, a successful implantation of HeartWare LVAD with concomitant ascending and sinus vasalva anuerysms repair has been described in previous research [8]. These experiences show that low mortality and morbidity after LVAD implantation can be achieved even in patients requiring combined surgical procedures.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, a successful implantation of HeartWare LVAD with concomitant ascending and sinus vasalva anuerysms repair has been described in previous research [8]. These experiences show that low mortality and morbidity after LVAD implantation can be achieved even in patients requiring combined surgical procedures.…”
Section: Discussionmentioning
confidence: 82%
“…It was demonstrated that the morphological RV (functional LV) can be cannulated using either diaphragmatic surface or the free wall without significant changes in standard implantation technique with good outcome [42]. Furthermore, HVAD can be successfully used in patients with heart failure requiring complex aortic pathologies [43].…”
Section: Hvad In the Presence Of Atypical Anatomy And With Concomitant mentioning
confidence: 98%
“…Medical management can be a starting option, targeting fluid overload with diuretics, reducing afterload with vasodilators ( 12 ) along with utilizing angiotensin-converting enzyme inhibitors, calcium channel blockers, or beta blockers ( 86 ).…”
Section: How To Manage Ar or Prevent De Novo Ar In...mentioning
confidence: 99%